2013
DOI: 10.1108/ara-03-2013-0017
|View full text |Cite
|
Sign up to set email alerts
|

Communication apprehension and communication self‐efficacy in accounting students

Abstract: (2013). Communication apprehension and communication self-efficacy in accounting students. Asian Review of Accounting, 21 (2), 160-175.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(32 citation statements)
references
References 69 publications
0
30
0
2
Order By: Relevance
“…It was also established that self-efficacy predicts students long-term achievement, (Parker, Marsh, Ciarrochi, Marshall, & Abduljabbar, 2014), which found that students mathematics self-efficacy is enhances them to face future challenges in life. Whereas, Hassall, Arquero, Joyce, and Gonzalez (2013) found the connection relations between self-efficacy and communication apprehension. Those who are self-efficacious on both oral and written communication tend to be highly efficacious in communicating with publics.…”
Section: Literature Reviewmentioning
confidence: 88%
“…It was also established that self-efficacy predicts students long-term achievement, (Parker, Marsh, Ciarrochi, Marshall, & Abduljabbar, 2014), which found that students mathematics self-efficacy is enhances them to face future challenges in life. Whereas, Hassall, Arquero, Joyce, and Gonzalez (2013) found the connection relations between self-efficacy and communication apprehension. Those who are self-efficacious on both oral and written communication tend to be highly efficacious in communicating with publics.…”
Section: Literature Reviewmentioning
confidence: 88%
“…The intervention, which takes place with foundation level undergraduate Accounting students, is underpinned by problem-based learning and contributing student pedagogy and focuses on the development of self-efficacy which has been identified to be a key area for the reduction of oral communication apprehension in public speaking contexts [6]. The paper will introduce the concept of communication apprehension in oral presentations and discuss causes and possible interventions.…”
Section: Original Citationmentioning
confidence: 99%
“…Despite the range of possible theories, a subset relate directly to the individual's expectations of success. These theories are often collectively termed expectancy-value theories [53] of which one, self-efficacy, has already been identified as having a close relation to OCA and particularly the public speaking element [6]. It is therefore an important part of the current framework, despite Illeris not mentioning self-efficacy in his model.…”
Section: Illeris's Three Dimensional Modelmentioning
confidence: 99%
See 2 more Smart Citations